Recent Trends in Customer Centricity: A Systematic Literature Review in Sustainability Economics - Arumdani, Ratna Sekar; Azhari, Fadhila Firdauzi; Fadhillah, Indah Nur; Dirgantara, I Made Bayu; Soetanto, Harry (Research Horizon, 2024)
This study aims to review recent literature published from 2014 to 2024 on customer centricity and the customer-centric paradigm in organisations, with particular emphasis on the integration of sustainability economics concepts to achieve long-term success. This research is in the form of a systematic literature review using the help of the watase uake site to filter articles that match the predetermined criteria. Article selection criteria include open full access text articles with publication dates no more than the last 10 years (2014-2024), and article sources must be articles published in reputable international journals from Q1 to Q4 based on the Scopus Rankings Index. The initial data obtained amounted to 315 articles, which were then filtered according to the criteria to produce 46 articles to be analysed in this study. The results of this study are expected to confirm the use of customer centricity and customer-centric in various research contexts with a variety of different terms, and highlight the importance of integrating sustainability economics in customer-centric strategies to create sustainable added value. Where in this study can be a literature that helps companies understand the concept of customer centricity more deeply in the context of sustainable economics.